Pengenalan ecoprint guna meningkatkan keterampilan siswa dalam pemanfaatan bahan alam - Susanto, Nindita Clourisa Amaris; Latief, Madyawati; Puspitasari, Ratih Dyah; Bemis, Restina; Heriyanti, Heriyanti (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Ecoprint is a technique for printing colors and shapes on fabric using natural materials. Ecoprint techniques have been introduced to junior high school students because they can capture the material and teacher's instructions independently, think critically and creatively. The purpose of the ecoprint introduction activity is to provide knowledge about ecoprint and students' skills in utilizing local potential through natural materials or plants around the school. The methods used are lectures, demonstrations, practice, and evaluation. The questionnaires and direct observations on ecoprint products were used as evaluations for this activity. Students have been able to print motifs and colors from leaves and flowers on a cloth to produce ecoprint products according to their respective creativity.Â